2017
DOI: 10.1186/s12936-017-1690-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical integrity and residual bio-efficacy of used LLINs in three cities of the South-West region of Cameroon 4 years after the first national mass-distribution campaign

Abstract: Background Long-lasting insecticidal nets (LLINs) are effective tools at reducing malaria transmission. In Cameroon, following the first national mass distribution campaign in 2011, there has been no follow up on the efficacy of LLINs distributed. The aim of this report is to assess the physical integrity and insecticidal potency of LLINs distributed in three cities with contrasting socio economic status (SES) and to evaluate the use and care for bed nets owned by individuals.MethodsThe study was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 18 publications
4
26
3
Order By: Relevance
“…Previous studies indicate that the efficacy of an ITN is close to 2 years. Current distribution campaigns are scheduled with the expectation that ITNs last 3 to 5 years, however more frequent replacement of ITNs is recommended [27][28][29][30][31][32][33]. The ITN distribution campaigns in Malawi are currently conducted every 3 years, which may be insufficient to maintain decreases in infection prevalence in children under 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that the efficacy of an ITN is close to 2 years. Current distribution campaigns are scheduled with the expectation that ITNs last 3 to 5 years, however more frequent replacement of ITNs is recommended [27][28][29][30][31][32][33]. The ITN distribution campaigns in Malawi are currently conducted every 3 years, which may be insufficient to maintain decreases in infection prevalence in children under 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the combination of LLINs and IRS with malathion (or treated NWH) could be trialed in South-West Cameroon as a resistance management strategy. The implementation of measures to supplement the distribution of LLINs is of more concern as it was shown that most of the LLINs distributed during the first national distribution campaign had lost both their physical integrity and insecticidal efficacy especially in Limbe and Buea [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also concerns on the increasing pyrethroid resistance which is likely to affect LLINs e cacy in preventing malaria parasite infection. Even though a study in Cameroon [15] as well as various studies in Malawi [16], Benin [17,18] and several countries in Africa [19] reported that LLIN still offers some protection even in areas of high pyrethroid resistance, there is need for continuous surveillance and evaluation on the effective use of LLINs distributed by the Cameroon government and its partners to reduce malaria mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%